2014
DOI: 10.1371/journal.pone.0089547
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Subunit of the System L1 Amino Acid Transporter (Slc7a5) Facilitates Nutrient Signalling in Mouse Skeletal Muscle

Abstract: The System L1-type amino acid transporter mediates transport of large neutral amino acids (LNAA) in many mammalian cell-types. LNAA such as leucine are required for full activation of the mTOR-S6K signalling pathway promoting protein synthesis and cell growth. The SLC7A5 (LAT1) catalytic subunit of high-affinity System L1 functions as a glycoprotein-associated heterodimer with the multifunctional protein SLC3A2 (CD98). We generated a floxed Slc7a5 mouse strain which, when crossed with mice expressing Cre drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 45 publications
2
117
0
Order By: Relevance
“…Phosphorylation of effector molecules in the insulin-like growth factor (IGF)-stimulated protein synthesis pathway, mTOR and S6RP, was significantly enhanced after combined activin B and myostatin prodomain treatment. In addition, RNA-Seq showed that complete inhibition of Smad2/3 signaling in muscle resulted in markedly increased expression of growth factor (Igf2, increased 2.4-fold), amino acid transport (Slc7a5, fourfold; Lat2, 3.8-fold), and amino acid biosynthesis (Psat1, 3.7-fold) genes critical for protein synthesis (33)(34)(35). In terms of protein degradation, the expression of the E3 ubiquitin ligases Fbxo32 (MAFbx/atrogin1), Trim63 (MuRF1), and Fbxo30 (Musa1) (7,22), which classically drive this pathway in muscle, was not substantially reduced after 8 wk of myostatin/activin blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of effector molecules in the insulin-like growth factor (IGF)-stimulated protein synthesis pathway, mTOR and S6RP, was significantly enhanced after combined activin B and myostatin prodomain treatment. In addition, RNA-Seq showed that complete inhibition of Smad2/3 signaling in muscle resulted in markedly increased expression of growth factor (Igf2, increased 2.4-fold), amino acid transport (Slc7a5, fourfold; Lat2, 3.8-fold), and amino acid biosynthesis (Psat1, 3.7-fold) genes critical for protein synthesis (33)(34)(35). In terms of protein degradation, the expression of the E3 ubiquitin ligases Fbxo32 (MAFbx/atrogin1), Trim63 (MuRF1), and Fbxo30 (Musa1) (7,22), which classically drive this pathway in muscle, was not substantially reduced after 8 wk of myostatin/activin blockade.…”
Section: Discussionmentioning
confidence: 99%
“…LAT4 is expressed in placenta, kidney, liver and small intestine (25,(31)(32)(33)(34)(35). Table 1 presents an overview of the tissue distribution of LAT1, LAT2, LAT3, LAT4 and LAT5 (26,28,29,(31)(32)(33)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these transporters have potential as drug targets in cancer therapy. In contrast, deletion of Slc7a5 in mice is embryonically lethal (49). This transporter is essential for the transfer of amino acids from blood into brain across the blood-brain barrier, suggesting a critical role for the transporter in the function and development of the brain.…”
Section: Utility Of Amino Acid Transporters Inmentioning
confidence: 99%